The relationship between obstructive sleep apnea and osteoarthritis: evidence from an observational and Mendelian randomization study - Yang, Zhe; Lv, Tian; Jin, Linna; Lv, Xiaoheng; Zhu, Xiaoying; Wang, Xiaoling; Zhang, Lisan; Tu, Chenghan; Chen, Shiqin; Yan, Xiongwei (Frontiers in Neurology, 2024)
Objectives Obstructive sleep apnea (OSA) and osteoarthritis (OA) are common comorbidities that significantly impact individuals’ quality of life. However, the relationship between OSA and OA remains unclear. This study aims to explore the connection between OSA and OA and evaluate causality using Mendelian randomization (MR). Methods A total of 12,454 participants from the National Health and Nutrition Examination Survey (2009–2012) were included. OSA participants were identified based on self-reported interviews. The association between OA and OSA was assessed through multivariable logistic regression analysis. A two-sample MR was employed to investigate the relationship between OSA and OA, specifically hip OA and knee OA, utilizing the inverse variance-weighted (IVW) approach. Results Based on the observational study, individuals with OSA exhibited a higher risk of OA (OR = 1.67, 95% CI = 1.40–1.98). IVW demonstrated that the risk of OA (OR = 1.13, 95% CI: 1.05–1.21, p = 0.001), hip OA (OR = 1.11, 95% CI: 1.04–1.18, p = 0.002), and knee OA (OR = 1.08, 95% CI: 1.02–1.14, p = 0.005) was significantly associated with OSA. Reverse MR analyses indicated no effect of OA on OSA. Additionally, body mass index (BMI) was found to mediate 36.9% (95% CI, 4.64–73.2%, p = 0.026) of the OSA effects on OA risk. Conclusion The cross-sectional observational analysis unveiled noteworthy associations between OSA and OA. Meanwhile, findings from the MR study provide support for a causal role.